2015
DOI: 10.1016/j.amsu.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of conservative treatment after stable post-traumatic thoracolumbar fractures in elderly: Is it really best option for all elderly patients?

Abstract: ObjectiveThe purpose of this study was to research the effectiveness of conservative treatment of stable post-traumatic thoracolumbar vertebral fractures in elderly patients.MethodsThe study included 21 elderly patients (13 females, 8 males) with post-traumatic thoracolumbar compression fracture who were treated with a brace. Fractures without any trauma history, pathological fractures, patients younger than 60 years old and patients with no malignancy history were excluded from study. Neurological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The luminal epithelium subtype is the most common molecular type of breast cancer. Due to the positive expression of hormone receptors in this type of tumor, it is sensitive to tamoxifen treatment, 21 which shows a good prognosis and long disease-free survival. The results of this study indicated that the luminal epithelium subtype contrast enhancement pattern is usually present as radial edge.…”
Section: Discussionmentioning
confidence: 99%
“…The luminal epithelium subtype is the most common molecular type of breast cancer. Due to the positive expression of hormone receptors in this type of tumor, it is sensitive to tamoxifen treatment, 21 which shows a good prognosis and long disease-free survival. The results of this study indicated that the luminal epithelium subtype contrast enhancement pattern is usually present as radial edge.…”
Section: Discussionmentioning
confidence: 99%
“…Although the survey had many limitations, it was still able to highlight the importance of age while planning surgical intervention. Another study by Cankaya et al 26 highlighted the importance of age when managing elderly patients with thoracolumbar fractures. Although none of his 21 patients underwent surgery, he concluded that age > 71 years was a strong predictor of complications.…”
Section: ) Age and Bone Strengthmentioning
confidence: 99%
“…Brace is a noninvasive option to support and correct spinal deformity or instability. However, ineffective restoration of spinal deformity and poor brace tolerance had been demonstrated in elderly patients with thoracolumbar VCFs treated with conservative treatments [3]. Percutaneous vertebroplasty and kyphoplasty are currently the primary minimally invasive surgical treatments for thoracolumbar VCFs [4].…”
Section: Introductionmentioning
confidence: 99%